Distinct characteristics of cloud-to-ground lightning electric fields generated in Malaysia - Hamzah, Muhammad Noh (2015)
Lightning generates electric fields that propagate through the vicinity of the atmosphere that have negative consequences especially to power, electronic and communications systems. Knowledge to the types of lightning and their characteristics must be acquired to fulfil the task of mitigating lightning problems. Most studies regarding the topic were done in temperate and sub-tropic regions. Thus, this study seeks to uncover better understanding of the lightning generated electric fields of cloud-to-ground lightning flashes observed in Malaysia in the tropics. Measurements of the generated fields were done using parallel plate antenna coupled with a recording system during the months of May, June and October 2013 at the premises of Universiti Putra Malaysia. The measurement site has a geographical coordinate of 2°59'19.9"N latitude and 101°43'29.8"E longitude, situated in Serdang, Selangor area. Malaysia generally has a tropical climate with maximum monsoon rain occurring from October due to southwest monsoon and intermonsoon period which affects the Selangor. The locations of some of the flashes were obtained from the Tenaga Nasional Berhad Research which is a research centre for the largest local power utility company, Tenaga Nasional Berhad using their Fault Analysis and Lightning Location System. This thesis presents the characteristics of lightning generated vertical electric field waveforms recorded in Malaysia. A total of 115 negative lightning and 57 positive lightning found with preliminary breakdown pulses, return strokes and chaotic pulse trains were present and analysed. The main findings of this study include characteristics of preliminary breakdown pulses, unusually long duration return strokes lasting more than 1 ms per stroke, occurrence of positive lightning and chaotic pulse trains in Malaysia with average durations of 335.12 μs for both negative and positive lightning combined, high multiplicity of positive lightning return strokes having an average multiplicity of 3.86, short interstroke intervals of positive lightning with an arithmetic mean of 25.03 ms, occurrence of chaotic pulse trains in positive lightning and unusual occurrences of chaotic pulse trains in terms of their placement in both types of lightning. In conclusion, the findings of the electric field generated in Malaysia were found to be distinct in many ways that adds to new knowledge from the findings previously mentioned. This is important as the kind of lightning activity affects the way in which protection systems are made.